The relationship between Gram-negative colonization and bloodstream infections in neonates: a systematic review and meta-analysis. (March 2018) - Folgori, L.; Tersigni, C.; Hsia, Y.; Kortsalioudaki, C.; Heath, P.; Sharland, M.; Bielicki, J.
Abstract: Objectives: Neonates admitted to neonatal intensive care units (NICU) are at significant risk of developing bloodstream infections (BSIs). Gram-negative bacteria (GNB) both colonize and infect, but the association between these entities is unclear. By conducting a systematic literature review, we aimed to explore the impact of factors on the association between GN colonization and GN-BSI at both baby-level and unit-level. Methods: We searched Medline, Embase, and Cochrane Library. Observational cohort studies published after 2000 up to June 2016 reporting data on the total number of neonates (0-28 days) colonized with GNB assessed by rectal/skin swab culture and the total number of neonates with GN-BSI (same bacteria) were included. Studies were excluded if data on skin/rectal colonization, neonates, and GNB could not be identified separately. Meta-analyses along with multivariate meta-regression with a random-effect model were performed to investigate factors associated with the GN colonization and GN-BSI at baby-level and unit-level. Results: Twenty-seven studies fulfilled our inclusion criteria, 15 for the baby-level and 12 for the unit-level analysis. Study heterogeneity was high, with suboptimal overall quality of reporting assessed by the STROBE-NI statement (44.8% of items adequately reported). In 1984 colonized neonates, 157 (7.9%) developed GN-BSI compared with 85 of 3583 (2.4%) non-colonized neonates. Considerable heterogeneity was observed across studies. Four factors were included in the meta-regression model: gross domestic product (GDP), pathogen, outbreak, and frequency of screening. There was no statistically significant impact of these factors on GN colonization and GN-BSI in baby-level. We were unable to perform the multivariate meta-regression because of insufficient reported data for unit-level. Conclusions: Study limitations include the small number and the high heterogeneity of the included studies. While this report shows a correlation between colonization and BSI risk, these data currently do not support routine screening for GNB. Analysis of large cohorts of colonized neonates with clinical outcomes is still needed to define the major determinants leading from colonization to infection.